Study and assessment of microbial communities in natural and commercial bioleaching systems. (1st October 2015) - Vardanyan, Arevik; Stepanyan, Samvel; Vardanyan, Narine; Markosyan, Levon; Sand, Wolfgang; Vera, Mario; Zhang, Ruiyong
Highlights: We studied biodiversity of chemolithotrophic bacteria in biotopes of Armenia. Bioleaching of pyrite is directly connected with adhesion ability of strains. We determined biochemical properties of bacteria regarding bioleaching of pyrite. Abstract: The exceptional diversity of ecogeographical conditions of Armenia and the richness of non-ferrous metals represent a great and valuable potential for the investigation of the biodiversity of acidophilic chemolithotrophic bacteria as well as for the isolation of new highly efficient strains and their communities. The studies of physiological and biotechnological properties of these relevant strains from the bioleaching communities will allow us to achieve comprehensive insight of interspecies relationships as a substantial prerequisite for the enhancement of the efficiency of biohydrometallurgical processes. In this study, novel strains of acidophilic chemolithotrophic bacteria belonging to genera Acidithiobacillus as well as Leptospirillum and Sulfobacillus have been isolated from sulfide ores of different geoformations in Armenia. The results showed that: (1) high efficiency of the isolated bacteria in bioleaching of pyrite was determined by their biochemical properties, especially enzyme activities involved in oxidation of ferrous iron and reduced inorganic sulfur compounds (RISCs). (2) Bioleaching of pyrite was directly connected with the ability of isolated strains to adhere on pyrite surfaces. Moreover, the efficiency of bioleaching of pyrite was correlated with the amount of adhered/attached bacterial cells of the isolated strains.